Principles of testing electronic systems - Mourad, Samiha (John Wiley & Sons, 2000)
A pragmatic approach to testing electronic systems As we move ahead in the electronic age, rapid changes in technology pose an ever-increasing number of challenges in testing electronic products. Many practicing engineers are involved in this arena, but few have a chance to study the field in a systematic way-learning takes place on the job. By covering the fundamental disciplines in detail, Principles of Testing Electronic Systems provides design engineers with the much-needed knowledge base. Divided into five major parts, this highly useful reference relates design and tests to the development of reliable electronic products; shows the main vehicles for design verification; examines designs that facilitate testing; and investigates how testing is applied to random logic, memories, FPGAs, and microprocessors. Finally, the last part offers coverage of advanced test solutions for today's very deep submicron designs.